GENOTYPING AND HEMOLYTIC CHARACTERIZATION OF PATHOGENIC BACTERIA FROM SOME RAW AND COOKED FOODS - Allaith, S. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study aimed to identify pathogenic bacteria in contaminated food from cafeterias and restaurants at the University of Kerbala. Thirty-nine bacterial samples were collected from various foods, such as salads, falafel, and meat products (burger, kebab, and shawarma), before cooking. Bacteria were serially diluted, isolated on selective media, and identified based on biochemical characteristics, and 16S rDNA sequencing. Hemolysin production, seen in most bacteria from raw food samples, was determined using blood agar. Genomic DNA was extracted from all bacterial samples, and their 16S rDNA were analyzed through PCR, gene sequencing, and phylogenetic tree construction. Twenty-seven genetic variants representing both gram-positive and gram-negative bacteria were identified. Most of the bacterial isolates produced α or β hemolysin and are likely important causes of food poisoning. These results highlight the need for strict quality control in the cafeterias and restaurants at the university, improving the public’s awareness of food safety issues, and possible routine medical examination of those who handle food at these locations.